Proceso de atención de enfermería a gestante de 45 años de 35 semanas de gestación con preeclampsia - Sellan Bustamante, Víctor Manuel (2022)
Preeclampsia is one of the most shocking complications of every pregnant woman that in most cases seriously endangers the mother-child binomial, even causing an increase in maternal and infant mortality rates, even more so when there are risk factors such as parity, advanced age to fertilize, in this particular case it is 45 years old, arterial hypertension of 175/100 mmHg, marked tachycardia of 140 beats per minute, edema of the lower limbs, headache, dyspnea and proteinuria. In the present case study Nursing Care Process for a 45-year-old pregnant woman at 35 weeks of gestation with preeclampsia, it was possible to carry out the nursing assessment and determine the health needs and prepare the nursing diagnoses to solve and satisfy the needs found according to to the functional patterns of Marjorie Gordon using the NANDA taxonomies as a fundamental guide, elaborating nursing diagnoses, NIC, applying nursing interventions and NOC, evaluating the results of the same, the taxonomies helped me to be able to fulfill the proposed objectives and, above all, to avoid potential complications to the mother-child binomial allowing the recovery of the health of pregnant women.